Efektivitas Model Teaching Games for Understanding (TGFU) terhadap Motivasi Belajar dan Partisipasi Aktif Siswa SMP pada Pembelajaran Handball - Parhan; Asep Sumpena; Alit Rahmat (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
ABSTRACT This study aims to examine the effectiveness of the Teaching Games for Understanding (TGfU) model on learning motivation and active participation of junior high school students in handball learning. The method used was a quasi-experimental design with a One Group Pretest-Posttest design, involving 80 eighth-grade students of SMP Negeri 3 Lembang selected through purposive sampling. The learning motivation instrument adapted the Perceived Locus of Causality Questionnaire (PLOCQ), while the active participation instrument adapted the Student Engagement in Schools Questionnaire (SESQ). Data were analyzed using the Shapiro-Wilk normality test and the Paired Sample t-Test. The results showed that students' learning motivation increased significantly, from a mean of 56.81 at pretest to 59.01 at posttest (Sig. = 0.001 < 0.05). In contrast, active participation increased from a mean of 101.55 to 102.38, but this increase was not statistically significant (Sig. = 0.330 > 0.05). In conclusion, the TGfU model is effective in improving students' learning motivation but has not yet shown significant effectiveness in improving active participation within a six-session treatment period. The TGfU model can be used as a student-centered alternative in physical education, although its implementation needs to be carried out more consistently and sustainably to optimally develop students' active participation. Keywords: Active Participation, Handball, Learning Motivation, Teaching Games for Understanding.